Uma Longa Viagem Pela América Latina: Invenção, Reprodução e Fundadores das Ciências Sociais. - Trindade, Helgio (Consejo Latinoamericano de Ciencias Sociales, 2021)
In the 1950s and, above all, between the 1960s and 1970s, Latin American social sciences acquired notable recognition at an international level, especially for the search for their own critical thinking and with a mixture of disciplines and theories. Hélgio Trindade's book reconstructs significant parts of this history and builds an essential and inevitable platform to continue investigating the social sciences in Latin America and the Caribbean. It is written by someone who was and was part of this process, both for his academic production and for his work in national and international academic organizations (CLACSO, AUGM, ANPOCS, IESALC/UNESCO, UNILA). That is, by a first-rate protagonist. I believe that at a time when -since the 1990s- Latin American critical thinking has lost the vigor of previous decades, Hélgio's book is a formidable contribution to the necessary recovery.